Unity 2D game development cookbook : over 50 hands-on recipes that leverage the features of Unity to help you create 2D games and game prototypes /: over 50 hands-on recipes that leverage the features of Unity to help you create 2D games and game prototypes. (2015) - Scolastici, Claudio
No abstract available